Development of continuous deglycerolisation reactor for ethyl ester production - Nikhom, Ruamporn; Waisuwan, Thanet; Klinpikul, Sunchai; Suthummanon, Sakesun; Supalakpanya, Kittiphoom; Tongurai, Chakrit (Engineering and Applied Science Research, 2015)
In this work, the development of continuous deglycerolisation (CD) reactor for ethyl ester production was investigated to improve the ethyl ester conversion. The device to assist separation of glycerol, in the CD unit, integrates transesterification (mixing zone) and separation (settling zone) into one unit. For reversible transesterification, removing glycerol during reaction can drive the equilibrium to the product side in order to achieve high conversion. Two models of device to assist separation of glycerol have been carried out to investigate the suitable conditions for ethyl ester production. Results showed that the fin-type model could separate higher amount of glycerol from the reaction system in order to achieve high transesterification conversion. The suitable conditions found in this study were: molar ratio of oil to ethanol of 1:5, KOCH3 concentration of 1.6 %wt. retention time of 15 min and reaction temperature of 70°C. At these conditions, ethyl ester’s purity and yield were 97.3%wt. and 92.0%wt., respectively. In addition, the fuel properties of the final ethyl ester product met the biodiesel standard for methyl ester which specified by Department of Energy Business.